2017
DOI: 10.1002/acr.23012
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Gout and Rheumatoid Arthritis Hospitalizations in Canada From 2000 to 2011

Abstract: Objective Gout and rheumatoid arthritis (RA) are the two most common forms of inflammatory arthritis worldwide. As hospitalizations for both conditions lead to substantial health resource use, contemporary inpatient trends and associated costs may provide important benchmarks of disease burden. However, relevant data are limited. Methods We used PopulationData BC, a population-based administrative dataset from Canada. We examined trends in the annual hospitalization and surgery rate of gout and RA from 2000-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 14 publications
5
26
0
Order By: Relevance
“…The declining trend in RA hospitalizations in our study is consistent with decreasing trends in orthopedic surgeries and hospitalizations for RA reported from different locations [ 8 11 , 19 ]. These reductions are mainly attributed to better management of RA including treating to target, early and more aggressive use of disease-modifying antirheumatic drugs, and introduction of biologic agents [ 6 , 9 ]. Although reductions in RA hospitalizations and hospital days imply decrease in RA hospitalization costs, this decrease likely indicates a shift in RA costs rather than reduction in RA total costs (i.e., reduction in hospitalization costs offset by rise in medication costs) [ 6 , 11 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The declining trend in RA hospitalizations in our study is consistent with decreasing trends in orthopedic surgeries and hospitalizations for RA reported from different locations [ 8 11 , 19 ]. These reductions are mainly attributed to better management of RA including treating to target, early and more aggressive use of disease-modifying antirheumatic drugs, and introduction of biologic agents [ 6 , 9 ]. Although reductions in RA hospitalizations and hospital days imply decrease in RA hospitalization costs, this decrease likely indicates a shift in RA costs rather than reduction in RA total costs (i.e., reduction in hospitalization costs offset by rise in medication costs) [ 6 , 11 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These improvements led to reductions in orthopedic surgeries and hospitalizations for RA in several countries [ 8 11 ]. By contrast, studies reported persistent suboptimal management of gout [ 12 , 13 ] with no improvement in premature mortality gap and rise in health care visits over recent decade [ 9 , 10 , 14 16 ]. Despite the rising burden of gout, to our knowledge, there is limited data on temporal trend in gout hospitalizations and its contrast with RA hospitalizations over recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, rheumatologists generally see gout as a chronic, very often progressive, condition that has acute flares but a tendency to progress. With gout increasing in prevalence, and with so many patients being older and affected by multiple comorbidities, gout is becoming more challenging to manage, as indicated (in part) by a marked increase in severe acute gout flares requiring hospitalization 52,53 . The G-CAN position is that the ACP's stance on ULT, essentially that ULT can be prescribed without urate monitoring or optimization of ULT dose to achieve urate concentrations below the saturation threshold of soluble urate 1 , is particularly troubling as it could help perpetuate the common practice pattern of underdosing of ULT 54 .…”
Section: Consequences Of Guideline Discordancementioning
confidence: 99%
“…Socioeconomic difficulties faced by hospitals are related to direct costs which involve examinations, laboratory tests, hospital admission, conventional synthetic and biologic disease modifying drugs, caregiver assistance, transportation and equipment. The improvement in RA symptoms through rheumatologist and nurse-led care (12), the use of conventional DMARDs instead of the more expensive biological therapy (13), the use of subcutaneous-injected biologic agents instead of the more expensive infused biologic therapy, a larger clinical setting with high patient volume involving a more efficient use of equipment (1), avoiding switching to another anti-TNF or to a biologic with a different mechanism of action (14), earlier treatment initiation, improved treatment strategies with conventional DMARDs, including triple therapy (3), negotiated cost discounts and utilization limits (15,16) can be used for cost optimization.…”
Section: Discussionmentioning
confidence: 99%